Empowering Teachers to Strengthen Pancasila Values through Textbook-Based Training - Prakoso, Prakoso; Rokhman, Fatkhur; Handoyo, Eko; Pramono, Suwito Eko (Proceedings of International Conference on Science, Education, and Technology, 2024)
This research aims to empower teachers to strengthen Pancasila values in high schools throughout Indonesia through textbook-based training integrated with the Experiential Learning Cycle (ELC). Pancasila, the basic ideology of the Indonesian state, plays an important role in shaping students’ character and national identity. However, challenges such as student disengagement, conventional teaching methods, and diverse backgrounds require innovative approaches. This research develops a comprehensive teacher training management model combining textbooks and ELC, encouraging more interesting and practical teaching methods. This methodology involves an extensive literature review to build a theoretical foundation, integrating subject knowledge with pedagogical strategies, reflective methodology, and empirical research. The research results emphasize the important role of textbooks in providing structured, consistent learning and comprehensive coverage of Pancasila values. Effective teacher training programs must integrate subject matter knowledge with innovative pedagogical strategies, employ reflective methodology, use comprehensive evaluation criteria, and encourage action research. This study advocates ongoing, collaborative, and subject-specific professional development for teachers. Applying Kolb’s Experience-Based Learning Theory enriches Pancasila education, making it more relevant and impactful for students. This approach ensures that teachers are well-equipped to deliver dynamic and effective Pancasila education, cultivating a generation of students embodying these important national values.